1984
DOI: 10.1148/radiology.153.2.6484168
|View full text |Cite
|
Sign up to set email alerts
|

Bolus geometry and dynamics after intravenous contrast medium injection.

Abstract: Studies of contrast medium bolus geometry and dynamics were carried out to provide data for optimizing the use of contrast medium in digital subtraction angiography (DSA) and dynamic CT. Apparatus for fast digital recording of x-ray attenuation profiles was used; this is a new digital imaging mode (Chronogram) available on a CT scanner. Variables studied were injection site, injection speed, contrast medium volume, and subsequent saline injection; peak time, full width at half maximum, and maximum contrast enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 0 publications
1
33
1
Order By: Relevance
“…8,9 Our study assessed the impact of injection parameters on an intra-arte- rial bolus of contrast medium, looking not only at the effects on arterial opacification but also at opacification of parenchyma and venous structures. The bolus geometry measured in the arterial capillary and venous phases represents the effects of the injection parameters modulated by the subject's physiology (eg, patient function).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Our study assessed the impact of injection parameters on an intra-arte- rial bolus of contrast medium, looking not only at the effects on arterial opacification but also at opacification of parenchyma and venous structures. The bolus geometry measured in the arterial capillary and venous phases represents the effects of the injection parameters modulated by the subject's physiology (eg, patient function).…”
Section: Discussionmentioning
confidence: 99%
“…Gd-MRA is performed using a three-dimensional gradient-echo acquisition [1][2][3][4][5][6]8,11). Three-dimensional computer modeling of such a sequence is computationally time intensive.…”
Section: Time-varying Intravascular Signalmentioning
confidence: 99%
“…Claussen et al reported that central lines produced an earlier peak aortic enhancement [12]. This probably caused some variability in our data.…”
Section: Study Limitationsmentioning
confidence: 59%